Analisis Laju Aliran Udara dan Laju Aliran Massa Bahan Bakar Terhadap Beban Pembakaran Sampah pada Incinerator Berbahan Bakar Limbah Oli Bekas - Junaidi Junaidi; Eddy Kurniawan; Abdika Lasmana (Jurnal Engine: Energi, Manufaktur, dan Material, 2021)
The amount of household waste and B3 from oil machine  waste have been increasing along with the increasing of polulation and the number of vehicles. This waste can be used as a source of energy. The aim of this research was to analize the air flow rate and mass flow rate of fuel in the incinerator oil machine waste using a burner furnace by conducting several variations of the experiment with variations in air velocity of 10,4 m/s (B1), 13,4 m/s (B2) and 14,3 m/s (B3) and fuel flow rate of 0,00408 l/s (A1) and 0,00838 l/s (A2) with fuel valve openings 1/2 and 1/4. The test results showed that the highest temperature was 1021,50C in the A2-B3 experiment with 45 minutes and the lowest temperature was obtained in the A1-B1 experiment which was 840,50C at the same time. In the incinerator test, the burning of dry plastic waste weighing 12 kg of waste burns out in 34 minutes with a temperature ratio for the burner furnace which is 780,90C and the incinerator chamber space is 480,70C and the combustion rate is 21,42 kg/hour. the yield of residual combustion is 9,32% and the incinerator combustion eficiency is 90,68% and for dry leaf waste weighing 8 kg the waste is burnt out in 20 minutes with a burner furnace temperature ratio of 712,30C and incinerator chamber space of 443, 20C and the combustion rate of 24,24 kg / hour and the yield of combustion residue is 96,94%.